Application of elementary school character education during the pandemic - Widyaningrum, Intan Fida; Firoh, Nur Alma; Umillah, Syakirotul Lian (Prosiding University Research Colloquium, 2021)
Character education is an effort to build character, supporting the social, emotional and ethical development of students assisted by parents, teachers, and communities that are essential in the development and development of character learners. Character education is still a topic of interest to this day. Education that must make the young generation intelligent and moral, is still, in fact, going to have to keep on striving to make it happen. In times of the current pandemic, the potential for children must be consistently polished and well socialized in order for every child's character to form and fully develop. Learning is nowadays done online, requiring children to use digital media. Digital media not only has a positive impact but also a negative impact that is a duty to educators, parents and communities in guiding and monitoring the child's digital media as best they can and thus benefiting themselves and their lives.